The Search for Violacein-Producing Microbes to Combat Batrachochytrium dendrobatidis: A Collaborative Research Project between Secondary School and College Research Students - Larra Agate (American Society for Microbiology, 2016)
In this citizen science–aided, college laboratory–based microbiology research project, secondary school students collaborate with college research students on an investigation centered around bacterial species in the local watershed. This study specifically investigated the prevalence of violacein-producing bacterial isolates, as violacein has been demonstrated as a potential bioremediation treatment for outbreaks of the worldwide invasive chytrid, Batrachochytrium dendrobatidis (Bd). The impact of this invasion has been linked to widespread amphibian decline, and tracking of the spread of Bd is currently ongoing. Secondary school students participated in this research project by sterilely collecting water samples from a local watershed, documenting the samples, and completing the initial sample plating in a BSL1 environment. In the second phase of this project, trained college students working in courses and as research assistants in the academic year and summer term in a BSL2 laboratory facility were able to use physiological, biochemical, and molecular techniques to further identify individual isolates as well as characterize their properties. Collaboration between these learning spaces provides an increased interest in the community for environmentally relevant research projects and allows for an expansion of the research team to increase study robustness. Journal of Microbiology & Biology Education